Squamous cell carcinoma at sites of old maxillary fractures. Issue 3 (June 2020) - Kawabata, Masaki; Nagano, Hiromi; Iuchi, Hiroyuki; Umakoshi, Mizuo; Ohori, Junichiro; Kurono, Yuichi
Abstract: Malignancies have been reported to occasionally arise in scar tissue following injury. One hypothesis involves prolonged overactivation of tissue repair systems due to chronic inflammation and irritation, although the pathogenesis of cancers occurring in scars is not fully understood. We describe here two cases with a history of maxillary fracture at the site where squamous cell carcinoma (SCC) subsequently developed. The first patient developed SCC 7 years after right maxillary fractures resulting from a traffic accident. He underwent chemoradiotherapy (70 Gy in 35 fractions) and maintained complete response (CR) for 10 months. The second patient developed SCC 3 years after sustaining right maxillary fractures in an ice hockey game. Radiotherapy and total maxillectomy were performed, but local recurrence arose and he has since been receiving chemotherapy.